Is generative artificial intelligence an ally of open science? - López-Borrull, Alexandre (Anuario ThinkEPI, 2024)
The article explores the relationship between generative artificial intelligence (GenAI) and open science, highlighting both its benefits and risks. GenAI can simplify complex scientific concepts, improve data management, and automate editorial processes, which could enhance open science. However, it also presents ethical challenges and risks, such as generating incorrect summaries, perpetuating biases, and creating low-quality content. The relationship between GenAI and open science is compared to biological interactions like mutualism and parasitism, suggesting that a balanced and collaborative approach is essential. Ethics and transparency are fundamental to ensure that open data is used responsibly and that the generated results are verifiable and reproducible.
Keywords: Generative artificial intelligence; Open science; Ethics; Research data